IMPLEMENTATION OF LOVE-BASED CHARACTER EDUCATION AT AULADUNA IT KINDERGARTEN, BENGKULU - Miza Syahfitri Jana; Emilianti; Sangkut Karunia Dwika; Cheiaka Septa Relita; Mice Sintia; Lifti Putri Ismadiana; Fidhia Andani (Journal Informatic, Education and Management (JIEM), 2026)
Character education at the Early Childhood Education (PAUD) level is the main foundation in the formation of children's personalities from the golden age . This study aims to describe the implementation of love- based character education at TK IT Auladuna Bengkulu, including the forms of activities , teacher strategies, and supporting and inhibiting factors in its implementation . This study uses a qualitative approach with a descriptive method . Data were collected through observation , interviews with the principal , teachers, and parents , and documentation studies . The research subjects consisted of 2 class teachers , 1 principal , and 15 group B students . The results of the study indicate that love -based character education is implemented through the habituation of compassion , teacher role models , thematic learning with Islamic nuances , and strengthening the values ​​of love for God, others , and the environment . This implementation has been proven to be able to improve children's social-emotional abilities , even though they are still faced with limited facilities and various family backgrounds . This study provides a practical contribution for PAUD teachers in designing love - based learning and theoretical contribution to the development of the concept of character education based on Islamic values ​​in early childhood